The establishment of an expected concentration reference range for eltrombopag in the individualized treatment of pediatric immune thrombocytopenia - Wang, Nan; Dong, Shuyue; Sun, Yixin; Liu, Jingjing; Wang, Zhifa; Ma, Jingyao; Wang, Xiaoling; Wu, Runhui; Cheng, Xiaoling (Frontiers in Pharmacology, 2025)
BackgroundDifferences in the clinical efficacy and adverse drug reactions (ADRs) of eltrombopag (ELT) in children with immune thrombocytopenia (ITP) may be positively correlated with the serum trough concentration of ELT. Individual pharmacokinetic variations primarily contribute to differences in ELT concentration among individuals. This study is the first to establish an expected concentration reference range for ELT in treating pediatric persistent/chronic ITP (P/CITP) across different age-groups.MethodsA total of 94 patients with 111 serum trough concentrations were analyzed to validate this range. The median age of patients was 7.68 (5.35, 10.21) years, and 44.7% (42/49) of them were male.ResultsSubgroup analyses revealed significant differences in ELT concentration related to the age, efficacy, and ADR occurrence. The expected concentration reference range was determined using the dose-related concentration (DRC) factor combined with the ELT dosage. The DRC factor ranges were as follows: 0.083–0.216 (mg/L)/mg in children aged 1–6 years, 0.058–0.125 (mg/L)/mg in children aged 7–12 years, and 0.043–0.097 (mg/L)/mg in children aged 13–18 years. Among patients with measured trough concentrations within the expected reference range, 84.3% (59/70) achieved response/complete response (R/CR) and 88.6% (62/70) did not experience ADR.ConclusionSerum trough concentration monitoring based on the established reference ranges could enhance the precision of individualized ELT therapy in pediatric ITP patients.